Reforming the hand that feeds you? Managing capacity development support in Cambodia and Malawi - Niels Keijzer (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
This paper analyses the policies and priorities of the governments of Cambodia and Malawi with respect to capacity development support (CDS), based on secondary research evidence and perceptions of effectiveness from a wide range of stakeholders. The study concentrates on the two governments' overall objectives and strategies on CDS and contrasts these to the situation in the health and education sectors, as two sectors that generate a strong need for capacity development and attract a significant portion of development cooperation. While CDS is provided in many forms, this study has restricted its analysis to dedicated events and advisory services. The study findings describe a political economy whereby all involved actors have few incentives to radically change the way in which CDS is managed. Instead, ineffective practices are largely reproduced over time, as none of the actors experience any direct costs or consequences for doing so, as well as no direct rewards for change. While some donors have introduced important reforms, the government remains best-placed to fundamentally break through this cycle of low effectiveness. As per these overall findings, this study concludes that it is not formal strategies and policy frameworks, but individual perceptions and attitudes of government officials that decisively influence the role and ability of CDS to support government and develop capacity. In aid-dependent and low-income countries such as Cambodia and Malawi, longer-term CDS interventions are more likely to be effective and sustainable when they promote adaptive and teamwork-oriented approaches under the leadership of strong and respected government officials.
Keywords: 330; Wirksamkeit und Evaluierung; Entwicklungsfinanzierung und öffentliche Finanzen